THE USE OF ELECTRONIC RESOURCES IN THE STUDY OF ENVIRONMENTAL DISCIPLINES - Саєнко, Т. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2018)
Priority of universities is to provide a broad introduction of information and communication technologies (ICT) in the educational process and the creation of a modern methodological support disciplines based on them. Today it is important to modernize the system of vocational training for future ecologists, postgraduate and continuous education using the powerful potential of electronic resources in all cycles of the curriculum. ICT facilitate the assimilation of a large body of knowledge, visualize large amounts of information, create better conditions and motivation for students' independent work. However, their use is often hampered by the lack of recommendations for the practical use and willingness of teachers to implement them. In European practice, distributed integrated thematic modular training programs, where each module combines educational, innovative and practical goals with a focus on solving specific problems. Such methods include raising the level of ecological consciousness, systematic environmentalization of various spheres of life and life support; adaptation of European standards of quality of life and environment to domestic conditions; formation of a national econet; modernization of the infrastructure of settlements; management of sustainable development of territorial socio-natural systems; measures for energy saving and optimization of energy consumption, etc. Development of educational, methodical and practical base should be carried out at the expense of development, application of electronic, multimedia and wide use of Internet resources.